Treatment of childhood tuberculosis: caregivers' practices and perceptions in Cape Town, South Africa. (February 2015) - Bélard, Sabine; Isaacs, Washiefa; Black, Faye; Bateman, Lindy; Madolo, Lucia; Munro, Jacinta; Workman, Lesley; Grobusch, Martin P.; Zar, Heather J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: A child's caregiver is key to the successful drug delivery and outcome of tuberculosis (TB) treatment. Understanding caregivers' practices and perceptions is important in the management of childhood TB. Objective: To investigate caregivers' practices and perceptions regarding TB treatment of children. Methods: A prospective, questionnaire-based study at Red Cross War Memorial Children's Hospital, Cape Town, South Africa of caregivers of children receiving TB treatment. During the children's follow-up visits at 1 (M1), 3 (M3) and 6 (M6) months after initiation of TB treatment, caregivers were interviewed face-to-face. Results: Caregivers of 253 children being treated for TB were interviewed and 434 surveys were completed between May 2011 and April 2013. 168 (39%) questionnaires were completed at M1, 165 (39%) at M3 and 94 (22%) at M6. Median age of children was 41 months (IQR 20–81). TB drugs were generally obtained from clinics most commonly visited 1–3 times a week. Only 86/162 (53%) and 109/155 (70%) children had been weighed at the clinic at M1 and M3, respectively. Drugs were most commonly administered after meals (69%). Two-thirds of interviewees crushed, dissolved or mixed the tablets with beverages or food. Most (88%) respondents reported easy drug administration. Few adverse drug reactions were reported. In 54/427 (13%) of surveys, concomitant antiretroviral treatment was given, most commonly before TB medication. Conclusion: Administration of TB drugs was regarded as easy, but differed substantially from recommended practice. Children were not weighed so that dosage could be adjusted, most caregivers crushed, dissolved or mixed the tablets with beverages or food, and administered medication after meals, all potentially contributing to sub-therapeutic drug levels.